The long-term role of the home learning environment in shaping students' academic attainment in secondary school. Issue 3 (21st September 2015) - Tracey Bywater, Dr; Sammons, Pam; Toth, Katalin; Sylva, Kathy; Melhuish, Edward; Siraj, Iram; Taggart, Brenda
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the relationships between the characteristics of the home learning environment (HLE) and students' academic attainments in secondary school in England at age 14 and 16. Design/methodology/approach – This research study uses multilevel statistical models to investigate the strength and significance of relationships between various measures of the HLE at ages three, six, 11 and 14, and students' academic attainment in secondary school. Findings – Multilevel models show that early years HLE and specific dimensions of later HLE are positive predictors of students' later academic attainment at age 14 and 16, when the influence of various individual, family and neighbourhood characteristics are controlled. Originality/value – The paper presents unique findings on the role of the HLE in shaping students' academic success at secondary school, including a range of measures of the HLE obtained at different ages. The results show that the early years HLE measured at age three continues to show effects on later attainment, over and beyond the effects of later HLE and other significant influences such as family socio-economic status and parents' qualification levels.